Open and Closed Endotracheal Suction Systems Divergently Affect Pulmonary Function in Mechanically Ventilated Subjects - Raimundo, Rodrigo Daminello; Sato, Monica Akemi; Silva, Talita Dias da; Abreu, Luiz Carlos de; Valenti, Vitor Engracia [UNESP]; Riggs, Daniel William; Carll, Alex Perrow (Daedalus Enterprises Inc, 2021)
BACKGROUND: In mechanically ventilated subjects, intra-tracheal secretions can be aspirated with either open suction systems (OSS) or closed suction systems (CSS). In contrast to CSS, conventional OSS require temporarily disconnecting the patient from the ventilator, which briefly diminishes PEEP and oxygen supply. On the other hand, CSS are more expensive and less effective at aspirating secretions. Thus, it was hypothesized that the 2 procedures differentially affect pulmonary and cardiovascular parameters after suction. METHODS: Subjects in the ICU (N = 66) were quasi-randomized for initial treatment with OSS or CSS in a crossover design. To compare the potential for these suction systems to compromise cardiorespiratory stability, changes in cardiopulmonary physiology were assessed from before to just after use of each suction system (three 10-s aspirations). RESULTS: For most pulmonary and cardiovascular parameters (ie, peak inspiratory pressure, airway resistance, pressure plateau, heart rate, and arterial pressures), the effects of aspiration inversely correlated with baseline values for that parameter, with a similar regression slope between suction systems. However, when controlling for baseline values, OSS caused significantly greater increases in airway resistance and peak inspiratory pressure (P < .001 and < .01 vs CSS, respectively). CONCLUSIONS: Elevated airway resistance prior to endotracheal suction may justify use of a CSS and contraindicate a conventional OSS in mechanically ventilated subjects. Adoption of this approach into clinical guidelines may prevent suction-induced pulmonary injury in subjects, especially for those with underlying diseases involving increased airway resistance or increased alveolar pressure.
Keywords: endotracheal aspiration; airway resistance; pulmonary compliance; mechanical ventilation; pulmonary pressure; lung